2008
DOI: 10.4049/jimmunol.181.7.4495
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral-Mediated Transcriptional Targeting of Dendritic Cells for Induction of T Cell Tolerance In Vivo

Abstract: Dendritic cells (DCs) are important APCs able to induce both tolerance and immunity. Therefore, DCs are attractive targets for immune intervention. However, the ex vivo generation and manipulation of DCs at sufficient numbers and without changing their original phenotypic and functional characteristics are major obstacles. To manipulate DCs in vivo, we developed a novel DC-specific self-inactivating lentiviral vector system using the 5′ untranslated region from the DC-STAMP gene as a putative promoter region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 47 publications
3
45
0
Order By: Relevance
“…To this end, we plan to examine the use of a prime-boost strategy, which is known to greatly increase the potency of DNA vaccinations. 38,39 Previously Dresch et al 13 have showed that lentiviral vector containing the 5 0 untranslated region of DC-STAMP yields long-term, DC-specific OVA expression in vivo. Moreover, their work confirms our data with respect to DC-STAMP promoter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, we plan to examine the use of a prime-boost strategy, which is known to greatly increase the potency of DNA vaccinations. 38,39 Previously Dresch et al 13 have showed that lentiviral vector containing the 5 0 untranslated region of DC-STAMP yields long-term, DC-specific OVA expression in vivo. Moreover, their work confirms our data with respect to DC-STAMP promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their work confirms our data with respect to DC-STAMP promoter. 13 To transcriptionally target DCs, we have isolated several novel promoters that have a DC-specific activity and are capable of driving antigen expression. Although we have focused on the induction of immunity by permissive expression of relevant antigen in DC, the additional introduction of signal transducers or cytokines using the same techniques may favorably influence the behavior of DCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been performed using hTERT mRNA or peptides transfected into DCs with different vectors, in which the adenovirus was the most popular vector employed (4-6). Until recently, HIV-1 derived lentiviral vectors (LVs) have emerged as powerful tools for gene delivery to a variety of dividing or non-dividing cells including DCs due to the high transfection rate (7)(8)(9)(10)(11)(12). To our knowledge, there are no studies available concerning DC vaccines transfected with the lentiviral vector encoding hTERT peptides.…”
Section: Introductionmentioning
confidence: 97%
“…Subsequently, clinical trials have shown the effectiveness of this approach for overcoming genetic deficiencies that manifest within the hematopoietic compartment such as X-linked severe combined immunodeficiency (X-SCID) and adenosine deaminase (ADA) deficiency. The technology used for such 'restorative' gene therapy can also be harnessed to target antigen expression to APC [62][63][64].…”
Section: Combining Hsct and Gene Therapy To Achieve Better Outcomesmentioning
confidence: 99%